Supply Chain Governance, Corporate Governance and Firm Supply Performance: A Paradox of Prediction - Mohd Saudi, Mohd Haizam; Supriadi, Hari; ., Sunjana; Ahmad Razimi, Mohd Shahril (ExcelingTech, 2019)
The supply chain management has emerged as a key competitive tool, however, little or no attention has been given to explore the link between supply chain governance, external corporate governance mechanism such as board characteristics and supply chain performance. Therefore, the current study is being carried out explore the relationship among three interlinked phenomena such as external corporate governance, supply chain governance and firm supply performance. It is argued in this study that the supply chain governance mediates the relationship between corporate governance firm supply performance. The SMART-PLS is used to achieve the objective of the current stud. The data is collected from the operation managers, production managers and finance managers of manufacturing firms listed in Indonesian Stock Exchange. The results of the study have shown a great deal of agreement with our proposed hypothesis. Meanwhile the findings have provided support to the predictions of agency theory and resource based theory. The study which is among pioneering studies on the issue will be helpful for policy makers and managers in understanding the role of agency theory in supply chain management.